Nancy Drew Season 3 disc 3 - McMann, Kennedy 1996-; Lewis, Leah 1996-; Jaizani, Maddison; Kasim, Tunji; Keene, Carolyn; CBS DVD (Firm) (Hollywood, California CBS DVD, 2022)
Season Three of Nancy Drew begins one week after the Season Two finale when we saw Nancy's mystical relative Temperance Hudson return to Horseshoe Bay with a dark agenda. Nancy's hopes of leaving her hometown for college will be derailed by this mysterious nemesis, and her fate will become entwined with that of her greatest foe yet. This season's adventures will bring Nancy and her friends' standalone cases, new love interests, and emotional journeys of self-discovery culminating in a showdown with Temperance, which results in a shattering turn that will profoundly change all of their lives. This must-have collection comes with all thirteen episodes from Season Three plus deleted scenes and a gag reel.
The confession of the long night -- The spellbound juror -- The witch tree symbol -- The ransom of the forsaken soul.
Title from disc label.
Based on the series Nancy Drew mystery stories by Carolyn Keene.
Originally broadcast as single episodes of a television program during in 2021.
Wide screen (16:9).
Includes special feature.
Kennedy McMann, Leah Lewis, Maddison Jaizani, Tunji Kasim, Alex Saxon, Riley Smith, Scott Wolf.
Keywords: Drew, Nancy -- (Fictitious character) -- Drama; Teenagers -- Drama; Criminal investigation -- Drama; Drama; Fiction television programs; Television adaptations; Television programs; Television series